Optimal dynamic scale and structure of a multi-pollution economy - Stefan Baumgärtner; Frank Jöst; Ralph Winkler (University of Heidelberg, Department of Economics, 2003)
We analyze the optimal dynamic scale and structure of a two-sector-economy, where each sector produces one consumption good and one specific pollutant. Both pollutants accumulate at different rates to stocks that damage the natural environment, which acts as a dynamic driving force for the economy. Our analysis shows that along the optimal time-path (i) the overall scale of economic activity may be less than maximal, (ii) the time-scale of structural change is mainly determined by the longer-lived pollutant, (iii) the optimal control of emissions may be non-monotonic. In particular the last result raises important questions about the design of optimal environmental policies.
Keywords: Q20; O10; O41; 330; dynamic economy-environment interaction; multi-pollutant emissions; non-monotonic control; optimal scale; stock pollution; structural change; time scales; Umweltökonomik; Mehrsektoren-Modell; Umweltbelastung; Skalenertrag; Intertemporale Allokation; Umweltpolitik; Theorie